De-Oiled Citrus Peels as Feedstock for the Production of Pectin Oligosaccharides and Its Effect on Lactobacillus fermentum, Probiotic Source - Sarkar, Rohan; Nain, Lata; Kundu, Aditi; Dutta, Anirban; Das, Debarup; Sethi, Shruti; Saha, Supradip (Frontiers in Nutrition, 2022)
Following the extraction of essential oil, citrus (Mousambi, Kinnow, and Orange) peel wastes were used to produce pectin. The yield of essential oil and pectin was maximum in orange. Pectin was characterized by Fourier-transform infrared spectroscopy (FT-IR) and X-ray diffraction (XRD) spectroscopy. The degree of esterification (DE) and methoxyl content (MC) was maximum in orange whereas, the equivalent weight was maximum in Mousambi. A significant increase (61.8%) in the Lactobacillus fermentum population was observed with pectin as compared with sugar. Three sources followed the Orange > Kinnow > Mousambi trend as a prebiotic source. It was attributed to higher DE as well as higher MC. Enhancement in the bacterial population was in the range of 79.16–87.50%. The present work confirms the potential of pectin as a probiotic source for the enhancement of the bacterial population. Thus, it has a large scope for use in the food industry targeting a circular economy.